2016
DOI: 10.1111/wre.12197
|View full text |Cite
|
Sign up to set email alerts
|

Interference of the agrestal Helianthus annuus biotype with sunflower growth

Abstract: The Helianthus annuus taxon includes the wild (ruderal), weedy (agrestal) and volunteer biotypes, which may share space and time with the sunflower crop. The agrestal biotype is one of the most harmful weeds challenging the use of modern biotechnological tools in sunflower. The interference of the agrestal biotype was studied at a range of weed densities within a sunflower crop. The area of influence of one agrestal plant was estimated as a circular area of more than 2.5 m 2 . The agrestal biotype at 10.7 plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
1
9
0
Order By: Relevance
“…Cultivated and wild sunflower largely differ in early growth (Hernández et al, 2020; Kost et al, 2015; Mercer et al, 2007), and phenotypic selection analyses suggest that an early rapid growth is advantageous in agricultural environments, therefore, it is expected to be selected rapidly (Kost et al, 2015; Presotto et al, 2019). In previous studies using BRW 07 , we showed that early rapid growth has probably evolved at the expense of lower stress tolerance in this biotype (Casquero and Cantamutto, 2016; Presotto et al, 2017), a similar pattern to that observed in North American weedy biotypes (Mayrose et al, 2011). Although we found no differences under competition with maize, the treatments we chose may represent an extreme competition, and also a low-resource environment, more typically found in non-agricultural than in agricultural environments (Mercer et al, 2007; Presotto et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Cultivated and wild sunflower largely differ in early growth (Hernández et al, 2020; Kost et al, 2015; Mercer et al, 2007), and phenotypic selection analyses suggest that an early rapid growth is advantageous in agricultural environments, therefore, it is expected to be selected rapidly (Kost et al, 2015; Presotto et al, 2019). In previous studies using BRW 07 , we showed that early rapid growth has probably evolved at the expense of lower stress tolerance in this biotype (Casquero and Cantamutto, 2016; Presotto et al, 2017), a similar pattern to that observed in North American weedy biotypes (Mayrose et al, 2011). Although we found no differences under competition with maize, the treatments we chose may represent an extreme competition, and also a low-resource environment, more typically found in non-agricultural than in agricultural environments (Mercer et al, 2007; Presotto et al, 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Under experimental field conditions, we observed that commercial rates of imazapyr adequately control ruderal and weedy sunflower at the 2-6 leaf stages, but at later developmental stages the herbicide only kills the main bud and most plants survive by developing the axillary buds, which partially restores fitness (unpublished data). This kind of tolerance is probably facilitated by the rapid emergence of wild and weedy sunflower after soil disturbance (Presotto et al, 2020) and the rapid initial growth of BRW (Casquero and Cantamutto, 2016; Presotto et al, 2017). Other mechanisms, such as late emergence, that avoid herbicide application (Darmency et al, 2017) cannot be ruled out, however, residual effects of the AHAS herbicides (Tranel and Wright, 2002) along with very low emergence of sunflower from the seed bank after spring (Presotto et al, 2020) make this mechanism less probable.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the biotypes with less cumulative emergence, in the undisturbed habitat, were BRW and the volunteer (Fig. 2; Table S2); both have larger seeds and higher oil content than ruderal populations (Casquero and Cantamutto 2016).…”
Section: Seed Emergence Increase With Disturbancementioning
confidence: 99%
“…For the species H. annuus, the weedy "agrestal" biotypes are considered natural cropwild hybrids [4,13,20,22]. The initial invasions of such biotypes on agricultural land might be attributed to importations of contaminated sunflower seed lots.…”
Section: Originmentioning
confidence: 99%
“…Shattercane and weedy sunflower are among the most competitive weeds against their closely related domesticated crop species, namely sorghum and sunflower, respectively [22,23]. Furthermore, both are troublesome species in a variety of crops.…”
Section: Introductionmentioning
confidence: 99%